Edukasi Pentingnya KB Implant Bagi Pus Di Dusun 3 Desa Pukdale Kecamatan Kupang Timur Kabupaten Kupang Tahun 2023 - Maria Magdalena Theofila Duka; Brigita Dina Manek; Deviserlina Babys (Pusat Riset dan Inovasi Nasional, 2023)
Family planning is one of the basic and primary preventive health services for women. Community service activities in this case educating the importance of family planning implants for PUS in Hamlet 03 Pukdale Village will be held on Saturday 25 March 2023 starting at 09.00 WITA. As implementing staff were 3 D-III midwifery supervisors from STIKes Maranatha Kupang with a total of 50 PUS participants. The activity began with an opening by the Head of Hamlet 03, followed by introductions to the activity implementation team. The socialization was opened by the team leader by explaining the aims and objectives of the socialization regarding the importance of implantable family planning education for PUS. Before starting, the team leader gave questions as a pre-test to the audience. Then the socialization is carried out by 1-2 presenters. Then the socialization is carried out by 1-2 presenters. Before the socialization ended, the extension team gave questions as a post-test. Then the activity was closed by the head of hamlet 03 Pukdale and this activity ended at 11.00 WITA.